2013
DOI: 10.1155/2013/614908
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Transforming Growth Factor-Beta 1 in Predicting the Occurrence of Diabetic Retinopathy in Juvenile Patients with Type 1 Diabetes Mellitus

Abstract: In the present study, we have decided to evaluate if serum transforming growth factor-beta 1 (TGF-β1) concentrations may have diagnostic value in predicting the occurrence of diabetic retinopathy (DR) in juvenile patients with type 1 diabetes mellitus (T1DM). The study included 81 children and adolescents with T1DM and 19 control subjects. All study participants had biochemical parameters examined, underwent an eye examination, and 24-hour blood pressure monitoring. Moreover, serum concentrations of TGF-β1 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…For example, in the fifteenth year of diabetes duration, an increase in the serum TGF- β 1 concentrations by 1 SD was associated with a 25% increase in the probability of microangiopathy when the remaining predictors were held constant. What is more, in our recent study we established the limit for TGF- β 1 concentrations on the presence of diabetic retinopathy in children and adolescents with T1DM [28]. We suggest that in patients with T1DM, TGF- β 1 levels may correlate with the degree of eye and kidney damage.…”
Section: Discussionmentioning
confidence: 89%
“…For example, in the fifteenth year of diabetes duration, an increase in the serum TGF- β 1 concentrations by 1 SD was associated with a 25% increase in the probability of microangiopathy when the remaining predictors were held constant. What is more, in our recent study we established the limit for TGF- β 1 concentrations on the presence of diabetic retinopathy in children and adolescents with T1DM [28]. We suggest that in patients with T1DM, TGF- β 1 levels may correlate with the degree of eye and kidney damage.…”
Section: Discussionmentioning
confidence: 89%
“…While we used serum-free X-VIVO 15 medium, Zielinski and colleagues (5) used RPMI 1640 medium supplemented with 5% human serum and they observed that TGF-β had no effect on human GM-CSF + CD4 + T cell differentiation (5). Because serum contains high levels of TGF-β that may be biologically active (37, 38), and bovine serum-derived TGF-β1 is 100% conserved compared to the human TGF-β1 protein, this might have precluded the possibility for the authors to study potential effects of exogenously added TGF-β (5). In the abovementioned study that described inhibitory effects of TGF-β on human GM-CSF + CD4 + T cell induction, the authors did not specify which medium and whether serum was used (9).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is some evidence that treatment with DPP-IV inhibitors interferes with the activation of TGF-ß1 [33]. The role of proinflammatory cytokine TGF-ß1 in the development of diabetic or hypertensive retinopathy appears controversial [34,35]. TGF-ß1 plays an important role in angiogenesis, endothelial cell proliferation, cell adhesion and the deposition of extracellular matrix [36,37].…”
Section: Discussionmentioning
confidence: 99%